2016
DOI: 10.4266/kjccm.2016.31.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Blood Conservation Strategy during Cardiac Valve Surgery in Jehovah's Witnesses: a Comparative Study with Non-Jehovah's Witnesses

Abstract: Background: Refusal of heterogenic blood products can be for religious reasons as in Jehovah's Witnesses or otherwise or as requested by an increasing number of patients. Furthermore blood reserves are under continuous demand with increasing costs. Therefore, transfusion avoidance strategies are desirable. We describe a historic comparison and current results of blood saving protocols in Jehovah's Witnesses patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…JW patients who received perioperative BCSs showed similar or better outcomes compared to patients who received blood transfusion [19][20][21][22]. In open knee surgeries, the postoperative complication rate was not significantly different between the JW (3.9%) and non-JW (3.2%) groups [20].…”
Section: Mortality Morbidity and Other Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…JW patients who received perioperative BCSs showed similar or better outcomes compared to patients who received blood transfusion [19][20][21][22]. In open knee surgeries, the postoperative complication rate was not significantly different between the JW (3.9%) and non-JW (3.2%) groups [20].…”
Section: Mortality Morbidity and Other Complicationsmentioning
confidence: 99%
“…They also showed that the infectious mortality rate was lower (30% vs. 40%) and the DIC incidence was lower (0.0% vs. 4.4%) in JW patients than in patients who received allogeneic blood transfusion [21]. In the study by Kim et al [22], the perioperative Cr level, as an indicator of renal injury, was not significantly different between the groups.…”
Section: Mortality Morbidity and Other Complicationsmentioning
confidence: 99%
“…These were 86%, 69%, 51%, and 34% at 5, 10, 15, and 20 years after surgery, respectively, vs. 74%, 53%, 35%, and 23% among non-Witnesses who received transfusions. Kim et al [55] found no significant difference in overall survival, stating the actuarial rates of overall survival at 1, 5, and 10 years to be 95.8% ± 4.1%, 85.6% ± 7.9%, and 85.6% ± 7.9% in the Jehovah's Witnesses group, respectively, and 100.0% ± 0.0%, 100.0% ± 0.0%, and 66.7% ± 27.2% in the non-Jehovah's Witnesses group (P = 0.313). Jassar et al [23] published the overall cumulative survival for their 91 Jehovah's Witnesses study cohort at 1 year and 5 years to be 87.9% ± 3.4% and 76.1% ± 5.4%, respectively.…”
Section: Mortalitymentioning
confidence: 99%
“…Guinn et al [57], Vaislic et al [52], Kim et al [55], and Whitson et al [58] provided 30-day mortality rates. This ranged from 0 to 4% in controls compared to 0-12% in patients who refused blood.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation